Caracterización e influencia de tiempo y temperatura sobre los destilados líquidos orgánicos obtenidos de carbones bituminosos y sub-bituminosos de la zona norte del perú - Cabrera Flores, Marzzia Julizza (2006)
The present work of investigation titled “Characterization and Influence of Time and Temperature on those Distilled Obtained Organic Liquids of Bituminous and Sub-bituminous Coal of the North Area of the Peru", it has for purposes to find the good parameters of temperature and time in the distillation, the characterization Physics-chemistry and the composition and identification of the present substances in these distilled of coal of bituminous and sub-bituminous type of the north area of the Peru, being particularized the study of samples belonging to two locations of these coal, located in Huaraz and a location located in Motupe in Lambayeque. For this one worked with a total of 5 samples of coal (A-1, A-2, B-1, B-2, C-1), two of the mine Sesuveca of the Peru in Ancash (A-1, A-2), two of the mine Zamora of Huaraz (B-1, B-2) and one of the mine Mining Contractors of Motupe in Lambayeque (C-1). It was carried out basic analysis of the coal for each one of the 5 samples being determined their Humidity, Volatile, Ashy Matter, Fixed Coal, to Be able to Heating, Sulfurate, these analyses were also reported in dry base, where you classifies according to the norms ASTM for the ranges of volatile matters in Bituminous and Sub-bituminous coal. In the distillation stage one worked for each sample of coal with 3 times (60, 90, 120) in minutes and for the temperature one worked with 3 temperatures (480, 550, 650) in °C, varying you among if and with two repetitions giving 18 tests as a result for each one of the samples; obtained those distilled to different times and temperatures the best were selected of each one of the 5 samples, and it was carried out their characterization Chemical-physics (Analysis of Melting Point and Boiling Point), then it was carried out the structural chemical characterization for the organic part one carries out analysis in UV-sense, GC-MS, for the part inorganic analysis of FAES and FAAS giving results of the diverse possible compounds inside those distilled of the types of coal of the study. Finally it is reported all the obtained data, and their due discussions, conclusions, recommendations of the investigation work carried out by means of statistical charts, figures, comparative charts, annexes and appendixes